Raising Knowledge Of Illocutionary Acts And Implicatures Used In A Thesis Examination Context For Students Of English Language Education Study Program - Margana, Author: (English Education Department, Universitas Islam Indonesia, 2012)
This paper deals with raising knowledge of the illocutionary acts and implied meanings for students of English education study program. It aims to describe the types of illocutionary acts, illocutionary forces, and conversational implicatures used in the thesis examination. Such types of knowledge should be well understood as the knowledge confers a clear description of the use of speech acts in the thesis examination. More specifically, students of English education study programs should be aware of the types of illocutionary acts, namely representatives, directives, commissive, expressive, and declarative which are further classified according to the illocutionary forces of each illocutionary act. Added to this, the knowledge of conversational implicatures: generalised conversational implicatures and particularised conversational implicature are also of great importance to minimise mis-conception and mis-interpretation of speech acts which possible occur in the thesis examination practices.Key words: illocutionary acts illocutionary forces implicatures